Guideline-recommended secondary prevention drug therapy after acute myocardial infarction: predictors and outcomes of nonadherence - Bauer, Timm; Gitt, Anselm Kai; Jünger, Claus Heinrich; Zahn, Ralf; Koeth, Oliver; Towae, Frank F. G.; Schwarz, Arne Kristian; Bestehorn, Kurt; Senges, Jochen; Zeymer, Uwe (European journal of cardiovascular prevention & rehabilitation, 2010)
BackgroundGuideline-recommended pharmacotherapy after myocardial infarction (MI) has been shown to reduce cardiovascular morbidity and mortality. Our objectives were to determine factors of, and to measure outcomes associated with nonadherence after MI.DesignMulticentre, prospective, observational study (Acute Coronary Syndromes Registry).MethodsWe analyzed data of 11 823 consecutive hospital survivors of acute MI and evaluated their discharge medication with the five following drugs: acetyl salicylic acid, clopidogrel, ?-blocker, angiotensin-converting enzyme inhibitor/sartan and statin. Patients receiving less than four drugs (group 1, n = 3439, 29.1%) were compared with those receiving 4?5 drugs (group 2, n = 8384, 70.9%). The impact of clinical, demographic and treatment factors on not prescribing each of these five drugs at discharge was investigated by using multiple logistic regression models.ResultsPatients of group 1 were older, had more comorbidities, more frequently suffered a nonST elevation MI and less often received reperfusion therapy. In the multivariate analysis, group 1 was associated with an increased risk for death at 1-year follow-up [odds ratio (OR): 1.6, 95% confidence interval (CI): 1.4?1.9]. After adjustment for confounding variables chronic oral anticoagulation was the strongest predictor for not receiving acetyl salicylic acid (OR: 19.6, 95% CI: 15.9?24.0) at discharge, no percutaneous coronary intervention within 48 h for not receiving statin (OR: 2.1, 95% CI: 1.9?2.4) and clopidogrel (OR: 10.4,95% CI: 9.4?11.5), chronic obstructive lung disease for not receiving ?-blocker (OR: 4.2,95% CI: 3.6?4.9) and chronic renal insufficiency for not receiving angiotensin-converting enzyme inhibitor/sartan (OR: 2.8, 95% CI: 2.2?3.5).ConclusionIn clinical practice guideline-adherent secondary prevention drug therapy is linked with an improved 1-year survival. Comorbidities and no interventional treatment were strong negative predictors for guideline-adherent discharge medication.
Gesehen am 15.12.2022